2019
DOI: 10.1038/s42004-019-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of self-assembly pathways to sheet or cage controlled by kinetic template effect

Abstract: The template effect is a key feature to control the arrangement of building blocks in assemblies, but its kinetic nature remains elusive compared to the thermodynamic aspects, with the exception of very simple reactions. Here we report a kinetic template effect in a selfassembled cage composed of flexible ditopic ligands and Pd(II) ions. Without template anion, a micrometer-sized sheet is kinetically trapped (off-pathway), which is converted into the thermodynamically most stable cage by the template anion. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…By screening of counter anions, it was found that NO 3 − is strongly bound in the cavity of the cage and that when the self‐assembly of the (NO 3 − ) [Pd 2 3 4 ] 4+ cage was conducted in the presence of NO 3 − , the sheet formation was prevented to give the cage in high yield. The template effect of NO 3 − was confirmed by the acceleration of the macrocyclization in the model complex, [ Pd 2 3 2 ] 4+ , from [ Pd Py* 2 ](BArF) 2 ( Pd indicates Pd(TMEDA) and BArF indicates [{3,5‐(CF 3 ) 2 C 6 H 3 } 4 B]) and 3 in the presence of NO 3 − (Figure 11a) [15b] . Note that NO 3 − has high enough coordination ability to promote ligand exchange of coordination bonds, which may also contribute to the acceleration of the formation of the (NO 3 − ) [Pd 2 3 4 ] 4+ cage.…”
Section: Qasap and Nasap For Pd(ii)‐linked Self‐assembliesmentioning
confidence: 88%
See 2 more Smart Citations
“…By screening of counter anions, it was found that NO 3 − is strongly bound in the cavity of the cage and that when the self‐assembly of the (NO 3 − ) [Pd 2 3 4 ] 4+ cage was conducted in the presence of NO 3 − , the sheet formation was prevented to give the cage in high yield. The template effect of NO 3 − was confirmed by the acceleration of the macrocyclization in the model complex, [ Pd 2 3 2 ] 4+ , from [ Pd Py* 2 ](BArF) 2 ( Pd indicates Pd(TMEDA) and BArF indicates [{3,5‐(CF 3 ) 2 C 6 H 3 } 4 B]) and 3 in the presence of NO 3 − (Figure 11a) [15b] . Note that NO 3 − has high enough coordination ability to promote ligand exchange of coordination bonds, which may also contribute to the acceleration of the formation of the (NO 3 − ) [Pd 2 3 4 ] 4+ cage.…”
Section: Qasap and Nasap For Pd(ii)‐linked Self‐assembliesmentioning
confidence: 88%
“…When the self‐assembly of the [Pd 2 3 4 ] 4+ cage was carried out with OTf − as the counter anion, the cage formation was dramatically retarded, [15b] suggesting that the counter anion affects the self‐assembly of the cage. It was found that the size of the kinetically produced sheet from [PdPy* 4 ](OTf) 2 and 3 is micrometer‐sized much larger than the size of the sheet prepared with BF 4 − and that the sheet was converted into the cage by the addition of BF 4 − , which indicates that the templation of the counter anion also contributes to the conversion of the sheet into the cage (Figure 11a).…”
Section: Qasap and Nasap For Pd(ii)‐linked Self‐assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…8i, middle) [79]. A solution study of CCs with flexible ligands also revealed that the encapsulation of appropriate anions is essential to selectively obtain a lantern structure over undesired polymerized products [239].…”
Section: Length and Flexibility Of The Ligandsmentioning
confidence: 99%
“…Molecular self-assembly is a phenomenon where building blocks assemble into a well-defined structure based on their intermolecular interactions and is a fundamental strategy to fabricate functional units and materials in biological and abiotic systems. The self-assembly mechanism is one of the research topics in molecular self-assembly because it is mysterious that the building blocks spontaneously assemble into an ordered structure as if they had intention and because the understanding of assembly mechanisms will make it possible to obtain novel assemblies that are inaccessible under thermodynamic control. Coordination self-assemblies are constructed by reversible coordination bonds that are made between organic multitopic ligands and metal ions. As their structures are simple compared to biological molecular self-assemblies, coordination self-assemblies are suitable models for the investigation of the self-assembly mechanism.…”
Section: Introductionmentioning
confidence: 99%